Left subclavian to descending aorta bypass: A less invasive extra‐anatomical solution for a type A interrupted aortic arch. Issue 10 (25th July 2019) - Garcia, Christopher; Rey, Jorge; Lopez, Alberto; Lamelas, Joseph; Orozco‐Sevilla, Vicente
Abstract: Interrupted aortic arch (IAA) is defined as a discontinuity of the aortic lumen from the aortic arch to the descending aorta. The incidence of this congenital malformation is three per million live births. It represents about 1.5% of congenital cardiac abnormalities. The classification system for IAA is divided into three distinct categories—type A: interruption of the lumen distal to the left subclavian artery, occurring in 43% cases; type B: interruption between the left carotid and left subclavian arteries, occurring in 53% cases (the most common); and type C: interruption between the innominate and left carotid, occurring in 4% cases. We describe the case of a 47‐year‐old woman who had a symptomatic type A IAA. A single‐stage extra‐anatomic bypass was performed between the left subclavian and the descending thoracic aorta using a 14 mm Dacron graft. The use of this approach is an option to solve this challenging clinical problem.